Sistema de supervisão e controle para interação assistiva humano-robô - Valadão, Carlos Torturella (2016)
Robotics are widely applied in several areas, such as industrial production, toys, machinery, some commercial services and also health, the main focus of this work. Currently, several causes can be pointed out as the responsibles for humans not being able to have adequate mobility and social interaction as well. Both mobility and interacion issues can impact negatively in the affected ones. This work proposes a robotic platform, which can assume two different configurations. It is used the wheeled mobile robot Adept Pioneer 3-DX that is the core of both system configuration. Each system is mounted using different pheripheral devices and structures, but the robot is present in both. The first configuration is a system that is used to help people with reduced mobility. An aluminum structure was made in order to turn the robot into a smart walker prototype. The idea is to use the whole device as an intelligent walker that is able to detect the distance and angle from the user’s legs and keep these parameters at the same values while walking with the user. It also offers weight bearing and balance supports, since there is an aluminum structure that holds partially the weight from the user and there is the robot that helps with the propulsion. The other proposed configuration is a friendly robot that can help autistic children to interact someway with the robot, as a social interaction robot. Since the robot is not a human and it is in a certain way more predictable than human beings, the children who suffer from ASD (Autism Spectrum Disorder) may feel more comfortable with the robot. The child-robot interaction can be a big step in the child’s development and there is even the possibility of using robots as a way of helping children to interact with machines and further help the interaction with humans. For both operation modes, there are control laws that were developed, such as the inverse kinematic controller for the system in the social interaction mode and the human-robot follower controller for the walker mode. Besides, there is a safety supervisor to ensure the users will not suffer any harm during the use of the system, in both modes. In addition, an interface common to both modes was developed to make the system easy to be used. For the social interaction mode, there is still a multimedia system that helps the children get entertained with the robot and pay attention to it.